Implications of aero-engine deterioration for a military aircraft's performance - Naeem, Muhamma (Cranfield University, 1999)
World developments have led the armed forces of many countries to become more aware of how their increasingly stringent financial budgets are spent. Major expenditure for military authorities is upon aero-engines. Some in-service deterioration in any mechanical device, such as an aircraft's gas-turbine engine, is inevitable. However, its extent and rate depend upon the qualities of design and manufacture, as well as on the maintenance/repair practices followed by the users. Each deterioration has an adverse effect on the performance and shortens the reliable operational life of the engine thereby resulting in higher life cycle costs. The adverse effect on the life-cycle cost can be reduced by determining the realistic fuel and life-usage and by having a better knowledge of the effects of each such deterioration on operational performance. Subsequently improvements can be made in the design and manufacture of adversely-affected components as well as with respect to maintenance / repair and operating practices. For a military aircraft's mission-profiles (consisting of several flight-segments), using computer simulations, the consequences of engine deterioration upon the aircraft's operational-effectiveness as well as fuel and life usage are predicted. These will help in making wiser management decisions (such as whether to remove the aero-engines from the aircraft for maintenance or to continue using them with some changes in the aircraft's mission profile), with the various types and extents of engine deterioration. Hence improved engine utilization, lower overall life-cycle costs and the optimal mission operational effectiveness for a squadron of aircraft can be achieved.